Does Improved Local Supply of Schooling Enhance Intergenerational Mobility in Education? : Evidence from Jordan - Assaad, Ragui; Saleh, Mohamed (World Bank, Washington, DC, 2016)
The impact of the growth of the local supply of public schools in the post-Colonial period on intergenerational mobility in education is a first-order question in the Arab World. This question is examined in Jordan using a unique dataset that links individual data on own schooling and parents' schooling for adults, from a household survey, with the supply of schools in the subdistrict of birth at the time the individual was of age to enroll, from a school census. The identification strategy exploits the variation in the supply of basic and secondary public schools across cohorts and subdistricts of birth in Jordan, controlling for year and subdistrict-of-birth fixed effects and interactions of governorate and year-of-birth fixed effects. The findings show that the local availability of basic public schools does, in fact, increase intergenerational mobility in education. For instance, a one standard deviation increase in the supply of basic public schools per 1,000 people reduces the father-son and mother-son associations of schooling by 18-20 percent and the father-daughter and mother-daughter associations by 33-44 percent. However, an increase in the local supply of secondary public schools does not seem to have an effect on the intergenerational mobility in education.